Assessment of response variables in bovine models of pain and stress, with and without meloxicam - Mosher, Ruby A. (Kansas State University, 2013)
The absence of pain management for common husbandry procedures, such as dehorning and castration of cattle, is considered to be an important animal welfare consideration, but there are currently no drugs approved by the FDA for the purpose of providing pain relief in cattle. The FDA’s Center for Veterinary Medicine (CVM) recognizes the need for the availability of pain-relieving drugs and has encouraged research into the development of behavioral and physiologic measures which can reliably demonstrate the effectiveness in that species. The USDA has also recognized this need by providing grants for research into investigating pain models for cattle that can be used for the development of pain mitigation methods. The studies reported in this dissertation were funded by the USDA and the American Association of Bovine Practitioners. They add to the body of knowledge from which a pain model in cattle may eventually be validated for use in the drug approval process and also contribute to knowledge base for a candidate non-steroidal anti-inflammatory drug for convenient use in cattle. The study reported in Chapter 2 was conducted to support research of a candidate pain-assessment variable, substance P. This study provides future researchers with recommended sample handling procedures for obtaining reliable and repeatable results, which is important if substance P is to be validated as pain biomarker in cattle. The study in Chapter 3 investigated the use of several variables for use in a pain model. The results provided researchers, veterinarians and policy-makers with evidence to support the common practice of castrating and dehorning calves at the same time rather than as individual procedures separated by a healing interim. The study in Chapter 4 investigated the pharmacokinetics of oral meloxicam when administered to juvenile ruminant and pre-ruminant calves. This study added to the growing knowledge base of the pharmacokinetics of oral meloxicam in cattle and also provided practitioners with practical information concerning the administration of the drug in milk replacer. Chapter 5 investigated the use of oral meloxicam in a production setting and indicated that meloxicam administration prior to surgical castration may reduce the incidence of respiratory disease in the post-surgical period.
Keywords: Veterinary science; Animal culture and nutrition; Pharmacology; Veterinary Medicine (0778)